Policy and Gay, Lesbian, Bisexual, Transgender and Intersex Students - Jones, Tiffany (Policy Implications of Research in Education ;, 2015)
This book addresses policy research on homophobic and transphobic bullying in schools. It covers quantitative and qualitative research into policy impacts for gay, lesbian, bisexual, transgender and intersex students. It draws on a large-scale Australian study of the impacts of different kinds of policy at the national, state, sector and school level. The study covers over 80 policies, interviews with key policy informants and survey data from 3,134 GLBTIQ students. Since new guidelines were released by UNESCO, homophobic and transphobic bullying in schools has become a key area of interest around the world. There has been much pressure on educational leadership to engage with these issues since the UN released international human rights legislation on sexual orientation and gender identity that have implications for student rights.The book presents statistically significant correlations between specific types of state and school level education policies that explicitly named homophobia/ GLBTIQ student issues, and lowered incidence of homophobic bullying, lowered risk of suicide and self-harm for these students. It includes stories from policy makers on how the policies came to be (through lawsuits, ministerial inquiries and political activism), right through to the stories of students themselves and how they individually felt the impacts of policies or policy lacks. International contexts of homophobic and transphobic bullying are discussed, as well as recent transnational work in this field. The book considers the different types of collaborations that can lead to further policy development, the transferability of the research and some of the benefits and problems with transnational policy adoptions.